Validity of Test: English Lecturers perceptions of Test Validity in Intensive Reading Course' Final Exam at Universitas Prima Indonesia in academic year 2022/2023 - Meisuri, M; Manik, Kresna Ningsih (West Science Interdisciplinary Studies, 2023)
This study was inspired from the researcher’ effort in order to enrich knowledge related to language testing’ component, one of component is validity and also curiosity to investigate the validity of Intensive Reading Final Test given by English lecturers in University of Prima Indonesia (UNPRI) in academic year 2022/2023. The research addresses two key questions: the lecturers’ perception of test validity in Intensive Reading Final Test in English Education Study Program of Teacher Training and Education Faculty of Universitas Prima Indonesia (UNPRI) and the reason of English lecturers in English Education Study Program of Teacher Training and Education Faculty of Universitas Prima Indonesia (UNPRI) Medan have such perceptions. This study applies qualitative research design in which involving 10 English lecturers at University of Prima Indonesia (UNPRI) as the respondents of this research, analyzing the perception of English lecturers related to validity of test in Intensive Reading Subject Final Exam. Findings shows that lecturers show their positive response to test validity with the information as follows: ALWAYS carry out an analysis of the question items before carrying out the Final Test” is in the percentage of 80%,  “FREQUENTLY carry out crosschecks between basic competencies and indicators determined in the questions” is in the percentage of 100 %, “ALWAYS (60 %) and FREQUENTLY (20%) Carry out reliability/consistency measurements (reliability)”, “ALWAYS (60%) Providing feedback on test results given to students. Lecturers take such action in preparing final semester exam questions for Intensive reading courses are: Analyzing test items is crucial in creating effective assessments, Feedback on tests is crucial for students' learning and development, crosschecking between indicators and test items to make sure that educational tests are valid and reliable, the reliability of question items critical for producing accurate, consistent, and trustworthy assessment results. It supports the meaningful interpretation of scores and allows for valid comparisons across individuals or groups. A way to make a high-test validity, it can be done in some ways such as compile the test grid before writing and selecting items to be tested, and making or selecting items on the test based on standard competence, basic competence, learning objectives that have been formulated in the syllabus